2019
DOI: 10.1111/tri.13406
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney transplant from deceased donors with acute kidney injury and prolonged cold ischemia time - a retrospective cohort study

Abstract: Summary While deceased donor renal transplants (DDRT) from donors with either acute kidney injury (AKI) or long cold ischemia time (CIT) are associated with increased risk of delayed graft function (DGF), recipients of these kidneys have good patient and allograft survival. There are limited data on whether kidneys with both AKI and long CIT have outcomes similar to kidneys with only one of these insults. Using data from the Scientific Registry of Transplant Recipients, we analyzed transplant outcomes in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
(51 reference statements)
3
24
1
Order By: Relevance
“…The increasing demand for allografts and growing waiting lists have led to the utilisation of organs from extended criteria donors (ECDs) or organs with prolonged ischemic times [1]. These organs are associated with higher rates of discard due to an anticipated increased risk of primary non function (PNF) or delayed graft function (DGF); therefore, novel dynamic preservation technologies are increasingly being adopted with the aim to allow organ utilisation in these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for allografts and growing waiting lists have led to the utilisation of organs from extended criteria donors (ECDs) or organs with prolonged ischemic times [1]. These organs are associated with higher rates of discard due to an anticipated increased risk of primary non function (PNF) or delayed graft function (DGF); therefore, novel dynamic preservation technologies are increasingly being adopted with the aim to allow organ utilisation in these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitations in creatinine kinetics in our data set, acute kidney injury (AKI) was defined in our study as a terminal creatinine >2 mg/dL and is an independent risk factor for discard that is associated with a higher proportion of discards than kidneys from donors without AKI (30% vs 18%, respectively) 37‐39 . However, there is now considerable evidence that AKI is often reversible and that kidneys from donors with AKI provide short‐ and long‐term graft survival and function comparable to kidneys with nonelevated terminal creatinine 37,40‐46 . Liu et al’s 47 recent comparison of propensity score‐matched deceased donors with AKI to deceased donors without AKI demonstrated that deceased donor AKI had no independent association with short‐term and long‐term recipient graft survival across all AKI stages.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] However, there is now considerable evidence that AKI is often reversible and that kidneys from donors with AKI provide short-and long-term graft survival and function comparable to kidneys with nonelevated terminal creatinine. 37,[40][41][42][43][44][45][46] Liu et al's 47 This study has several limitations. We rely on OPTN registry data, which may contain reporting errors.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…However, although both prolonged WIT and CIT have been found to increase risk of DGF in these organs, for major endpoints such as graft and patient survival, DCD kidneys with high WIT and CIT have not been found to carry significantly higher hazards when compared with DBD kidneys 5‐9 . These analyses, though, were performed prior to the implementation of the new Kidney Allocation System (KAS) in December 2014, after which average CIT increased and organ utilization patterns changed 10 . Given the proposed new allocation strategies that are likely to result in increased organ sharing, we attempt to determine whether WIT and/or CIT was associated with post‐transplant outcomes for DCD allografts in the post‐KAS era.…”
Section: Introductionmentioning
confidence: 99%